Nutritional Factors in the Prevention of Atopic Dermatitis in Children - Trikamjee, Thulja; Comberiati, Pasquale; D'Auria, Enza; Peroni, Diego; Zuccotti, Gian Vincenzo (Frontiers in Pediatrics, 2021)
Atopic dermatitis is one of the most frequent chronic skin diseases worldwide and often develops within the first few years of life. Recent advancements in our knowledge of its pathophysiology have brought to light the role of genetic predisposition and environmental triggers. With the increasing prevalence of allergic diseases, there is a strong need for a better understanding of the various modifiable eliciting factors of such conditions. The concomitant rise in food allergy and insights into the skin barrier function has highlighted the role of nutrition and diet in the prevention and modification of allergic disorders. Furthermore, the identification of the skin as an important route of sensitization, and the risk of progression to asthma later in life, stress the significance of optimizing our management of skin inflammation in the prevention of allergies. Many nutritional factors, including the type of maternal diet during pregnancy, the duration of breastfeeding, the epicutaneous exposure of allergenic food proteins in the first few years of life, the timing of the introduction of complementary foods, the supplementation of vitamins and probiotics/prebiotics during prenatal and early life, have been assessed as potential targets for the prevention of atopy and eczema. Here, we review the latest data addressing prenatal and perinatal nutritional and dietary interventions in the primary prevention of atopic dermatitis. Also, we define knowledge gaps and targets for future research in the prevention of atopic dermatitis.